(untitled) (Simbiótica. Revista Eletrônica, 2022)
This work analyzes in the film The lighthouse (2019), by Robert Eggers, the possibilities in the intertwining between two audio tracks: the music and the sound effect. The analyzes seek to understand the influence of these items on the narrative, their impact on the audience, and how they create an immersive experience, with their own symbolisms and meanings. To guide such analyzes, semiology concepts and authors will be used, in addition to other relevant areas. In passages of the film, illustrations and applications of the concepts covered will be evidenced, which promote the confirmation of the reported information. It is important to note that the audio track can not only be one of the elements that constitute an audiovisual work, but can also play a leading role, creating (re)meanings for the image and the narrative. Keywords: cinema; music; sound effects; semiology.